State Languages ​​in Georgia (Georgian, Abkhazian): Problems and Prospects - Gvantseladze, Teimuraz (Actual Problems of Kartvelology, 2025)
According to Article 8 of the Constitution of Georgia, "The state language of Georgia is Georgian, and in the Autonomous Republic of Abkhazia - also Abkhaz". At first glance, the legal status of the Abkhaz language is also regulated by the so-called constitution of Abkhazia, adopted on November 26, 1994 by the occupation regime of the region, according to which Abkhaz is considered the state language of the region, but at the same time Russian is declared the official language (Article 6). In fact, the document adopted by the occupation regime legitimized the unequal status of the Abkhaz and Russian languages ​​in favor of the latter, since: 1. Not only the majority of the non-Abkhaz population of the region does not speak the Abkhaz language, but also a large part of ethnic Abkhazians, especially the youth; 2. The functioning of the so-called educational system inherited from the Soviet Abkhaz school, in which children are not given the opportunity to study their native language after the primary level, creates a threat of denationalization of Abkhaz children and the disappearance of the Abkhaz language; 3. The Abkhaz language cannot compete with the Russian language, which is considered prestigious and more developed; 4. Both the population and the regime do not consider the Abkhaz language as a means of everyday communication, official mono-ethnic or interethnic communication, the language of culture and science...